improving students' reading comprehension through cooperative learning strategy - Eneng Liah Khoiriyah (Cakrawala Pedagogik, 2020)
Abstract The purpose of this research is to know whether cooperative learning can be used to improve students’ reading comprehension at SMK Ma’arif NU Pandeglang. Research hypothesis is to improve students’ reading comprehension through cooperative learning strategy. The method used in this research was takes descriptive qualitative which use cycle model, there are: plan, action, observation and reflection and use a Classroom Action Research (CAR) method. The data is gathered by giving test, multiple choice, and questioner. The result of the test obviously infers that there is contribution of using cooperative learning in improving students reading comprehension because have different score between cycle one and cycle two and get score hight than cycle one. Keywords: Reading Comprehension, Cooperative Learning